2007
DOI: 10.1158/1055-9965.epi-06-0766
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Fruit-Vegetable and/or Low-Fat Intervention on Breast Nipple Aspirate Fluid Micronutrient Levels

Abstract: Background: A change in diet is known to affect micronutrient levels in blood but to what extent diet can affect micronutrient levels in the breast is not yet well established. Methods: Healthy, premenopausal women with a family history of breast cancer were randomized across four diet arms for 1 year in a 2 Â 2 factorial design study: control, low-fat, high fruit-vegetable, and combination low-fat/high fruit-vegetable diets. Subjects were asked to collect breast nipple aspirate fluid (NAF) at 0, 6, and 12 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Several prospective or cohort studies have reported an inverse Vitamins [11,25] provitamin A [9] vitamin E [9] retinol [10,11,25] association between breast cancer risk and serum/plasma carotenoids, including a-and b-carotenes and lutein [59,60]. Despite being a relatively minor component among total carotenoids, it is intriguing that lutein showed a significant inverse association [25].…”
Section: Role Of Nutrients In Nipple Aspirate Fluids: Effects On Breamentioning
confidence: 99%
See 4 more Smart Citations
“…Several prospective or cohort studies have reported an inverse Vitamins [11,25] provitamin A [9] vitamin E [9] retinol [10,11,25] association between breast cancer risk and serum/plasma carotenoids, including a-and b-carotenes and lutein [59,60]. Despite being a relatively minor component among total carotenoids, it is intriguing that lutein showed a significant inverse association [25].…”
Section: Role Of Nutrients In Nipple Aspirate Fluids: Effects On Breamentioning
confidence: 99%
“…In this respect, a recent comprehensive study evaluates how a change in diet might affect micronutrient levels in the NAF breast microenvironment [10]. An important indication was that carotenoids in NAF increased with a high fruit and vegetable diet regardless of whether dietary fat intake was concomitantly decreased, but surprisingly little correlation between levels of micronutrients in NAF and plasma was found [10].…”
Section: Role Of Nutrients In Nipple Aspirate Fluids: Effects On Breamentioning
confidence: 99%
See 3 more Smart Citations